Safeguarding Patient Information as an Issue Faced by Nurses: A policy brief - Alireza Nikbakht Nasrabadi; Narges Norouzkhani; Arpi Manookian; Mohammad Ali Cheraghi; Mohsen Mohammadi; Zohreh Izadidastenaei; Amir Hossein Goudarzian (ACHSM, 2024)
In an era of advancing technology, nurses find themselves at the forefront of protecting patient information. Safeguarding patient information is a critical concern in healthcare settings due to the potential adverse effects that can result from breaches or mishandling of this data. This invasion of privacy can have profound emotional, social, and financial repercussions for patients. In this article, possible and effective approaches were provided under Evolving cybersecurity threats, balancing access and privacy, human error and insider threats, education and training, interoperability and data sharing headings. Patient information security is a complex and ever-evolving challenge for nursing professionals. Nurses must remain vigilant, well-informed, and proactive in implementing cybersecurity best practices.